The effects of early life pain and juvenile fear conditioning on CRF-receptor expression in the amygdala and hypothalamus of the juvenile rat - Michael A. Burman; Jared T. Zuke (PLoS ONE, 2026)
Early life pain and stress have lasting consequences on nervous system development that can interact with later stress or trauma to create a susceptibility to fear, anxiety, depression and chronic pain among other psychological disorders. Recent work has identified changes in corticotropin releasing factor signaling in limbic system structures, such as the amygdala and hypothalamus, as a key mechanism behind these changes – albeit in a sex-dependent manner. CRF has two major receptors, CRFR1 and CRFR2 which have also been shown to play key roles in fear and pain expression. The current work examines the effects of early life pain designed to mimic the neonatal medical trauma that occurs in the Neonatal Intensive Care Unit (NICU), paired with a juvenile trauma in the form of fear conditioning, on expression of crhr1 and crhr2 mRNA in the central nucleus (CeA) and basolateral nucleus (BLA) of the amygdala as well as the paraventricular nucleus (PVN) and ventromedial nucleus (VMH) hypothalamus of the juvenile rat. While prior work has demonstrated that early life pain significantly impacts expression of the CRF ligand mRNA, this study examines the effects of early life pain and stress, as well as adolescent fear conditioning, on CRF receptor expression. The data demonstrate that early life pain and fear conditioning have only modest effects on CRF receptor expression in the amygdala and hypothalamus in a sex dependent manner. In both sexes, fear conditioning increased crhr2 mRNA in the CeA only in neonatally undisturbed subjects. In addition, there was a trend towards altered crhr2 mRNA following neonatal manipulation in the PVN. In females specifically, we observed significant changes in crhr2 mRNA expression following fear conditioning in the right BLA. There were no female-specific changes following neonatal pain and stress. In males, we observed significant changes in crhr1 mRNA in the posterior PVN and trends toward changes in crhr2 mRNA in the CeA and VMH following neonatal manipulation. Together, these data confirm prior work that early life pain and stress alter the neural circuitry of pain and stress in a sex-specific manner. However, given the limited changes observed, in it unlikely that CRH receptor alterations are a major mechanism of action of early life pain.